Decay kinetics-based precise feeding enables long-term preservation of anammox granular sludge - Chao Pan; Junwei Wu; Dongdong Xu; Shuang Pei; Leiyan Guo; Da Kang; Changyong Wu; Ping Zheng; Meng Zhang (Water Research, 2026)

Stage-dependent dual effects of folic acid in esophageal squamous cell carcinogenesis: precancerous lesions as a potential transition point - Niannian Wang; Da Pan; Xingyuan Ren; Shiyun Wan; Huan Zhang; Xiangjun Chen; Shaokang Wang; Guiju Sun (Food Research International, 2026)

Combined exposure to wildfire ash and road salts reshapes skin and gut microbiota and reduces fitness in amphibians - Qing Tong; Qiu-ru Fan; Hong-xin Jiang; Yue-liang Pan; Wen-jing Dong; Ming-da Xu; Zhi-wen Luo; Li-yong Cui (Environmental Research, 2026)

Physiological and molecular mechanisms of blue light-regulated archeospore formation in Pyropia yezoensis - Li-Fei Yang; Yue-Ting Pan; Hong-Chang Ding; Da-Hai Gao (Aquaculture, 2026)

Structure-dependent regulation of nanoplastic uptake by humic substances in a freshwater protozoan - Ke-Da Zhang; Hong-Jie Zhang; Xin-Yuan Li; Wei Pan; Xin-Lei Wang; Ai-Jun Miao (Water Research, 2026)

Inferential modeling of dry deposition across the Ammonia Monitoring Network (AMoN) - Colleen B. Baublitz; John T. Walker; Zhiyong Wu; Jesse O. Bash; Michael D. Bell; Da Pan (Atmospheric Environment, 2026)

Water release regulating JsSWEET17 transcriptional expression to promote the female flower bud differentiation of Juglans sigillata - Wenwen Li; Da Yuan; Jinyan Chen; Chunxiang Li; Yuanqi Huang; Wen'e Zhang; Xuejun Pan (Journal of Plant Physiology, 2026)

Minimum mortality temperature by cause of death and age group: A multi-country observational study (1990–2019) - Seunghyun Eom; Aurelio Tobias; Masahiro Hashizume; Daewon Yang; Claire Demoury; Eric Lavigne; Aleš Urban; Klea Katsouyanni; Francesco Sera; Paul Lester Carlos Chua; Susana das Neves Pereira da Silva; Dominic Royé; et al. (Environmental Research, 2026)

Recovery trajectories of amphibian skin microbiota following ash exposure across translocation and natural recovery scenarios - Qing Tong; Qiu-ru Fan; Hong-xin Jiang; Ming-da Xu; Yue-liang Pan; Li-yong Cui (Environmental Pollution, 2026)

Near-surface viscoelastic FWI using body and surface-waves with irregular topography - Wen-yong Pan; Ya-da Wang (Applied Geophysics, 2026)

Minutes-long soft X-ray prompt emission from a compact object merger - An Li; Chen-Wei Wang; Niccolò Passaleva; Jie An; Bin-Bin Zhang; Eleonora Troja; Yi-Han Iris Yin; Yuan Liu; Shao-Lin Xiong; Li-Ping Xin; Yi-Xuan Shao; Jun Yang; et al. (Science Bulletin, 2026)

Synergistic design of oxygen-rich and microporous biomass derived carbon for the catalytic adsorption of cyanide gases - Yali Wang; Mingzhe Ma; Shicai Liu; Xueyuan Pan; Yanren Jin; Ting Zhao; Ao Wang; MengMeng Fan; Da Li; Kang Sun; Jianchun Jiang; Hao Sun (Journal of Environmental Chemical Engineering, 2026)

Natural deep eutectic solvents assisted the encapsulation of curcumin in gellan gum hydrogels - Yu-Nan Pan; Jia-Cheng Liu; Lin-Da Zhang; Bin Lai; Ce Wang; Jia-Nan Yan; Hai-Tao Wu (Food Research International, 2026)

A clinically practical aging clock (physical clock) for healthy aging: development, validation, and application for health assessment and intervention - Xiao-Ming Wang; Jing Pang; Xue Yu; Xuewei Zhang; Shi-Bo Wang; Qi Pan; Aiqun Chen; Lengnan Xu; Nan Li; Xuefei Li; Yao Wang; Yujia Gu; et al. (Science China Life Sciences, 2026)

On Estimating the Convection Velocity in Turbulent Canopy Flows - Da-Kai Peng; Ying Pan (Boundary-Layer Meteorology, 2026)
For atmospheric turbulence, multiplying an estimate of the convection velocity with the integral time scale is useful for estimating the integral length scale. Velocity scales that have been used to estimate the convection velocity include the local mean velocity, the ratio of e -folding length and time scales, the approximations of the slope of an elongated band of space-time autocorrelation isocontours, and the phase speed of Fourier modes. A knowledge gap is the lack of evaluation of these velocity scales directly against the convection velocity, especially for canopy flows where previous studies have reported somewhat inconsistent results. The objective of this work is to assess the ability of the local mean velocity and each autocorrelation-based velocity scale to estimate the convection velocity of velocity components in canopy flows. Firstly, large-eddy simulation (LES) results of neutral canopy flows are used to compare these velocity scales to directly quantified convection velocity. When the direction of interest roughly aligns with the local mean velocity (specifically, for an angle of $$7.5^° $$ 7 . 5 ∘ or smaller), all autocorrelation-based velocity scales generally agree better with the convection velocity than the local mean wind component. When the direction of interest departs from the local mean velocity for more than $$15^° $$ 15 ∘ , the ability of each velocity scale to approximate the convection velocity changes substantially. Secondly, data collected during the Canopy Horizontal Array Turbulence Study (CHATS) are used as an example of interpreting estimates of the convection velocity in the field with the guidance from LES findings. The guidance focuses on uncertainties of velocity scale estimates and potential caution needed when using these estimates.

The undescribed alkaloids from Jacobaea cannabifolia (less.) E. Wiebe and their anti-inflammatory activities - Jian-Zhe Li; Juan Pan; Yu Bi; Zhi-Chao Hao; Wei Guan; Hai-Xue Kuang; Qing-Shan Chen; Li-Li Zhang; Xin-Yue Wu; Da-Lin Li; Bing-You Yang; Yan Liu (Natural Product Research, 2026)

A digital-enabled circular recovery system for post-consumer inhalers: Linking material recovery, behaviour, and carbon reduction - Huong Thanh Hoang; Luong Cao Tung Son; Yu-Fen Huang; Ren-Hao Pan; Phuong Truc Nguyen Le; I-Chun Chuang; Huang-Chi Chen; Hung-Pin Tu; Chih-Hsing Hung; Da-Wei Wu (Journal of Cleaner Production, 2026)

Copolymer hydrogel formed by κ-carrageenan and chickpea protein amyloid fibrils: From rheological properties to regulation of aggregation morphology - Lin-Da Zhang; Xiao-Lei Zang; Yu-Nan Pan; Jia-Cheng Liu; Jia-Nan Yan; Bin Lai; Ce Wang; Hai-Tao Wu (Food Hydrocolloids, 2026)

Ammonia in northeast Colorado is increasing, rising most quickly in regions close to confined animal feeding operations - Lillian E. Naimie; Kimberley A. Corwin; Da Pan; Emily V. Fischer; Amy P. Sullivan; Katherine B. Benedict; Lena Low; Jeffrey L. Collett (Atmospheric Environment, 2026)

VALD-3 Induces GSDME-Dependent Pyroptosis via ROS/JNK/Bax Pathway in Triple-Negative Breast Cancer Cells - Xuhui Zhao; Xuhong Pan; Weijie Ma; Shuang Liang; Dezhuan Da; Jiawei Liu; LingFang Zhang; Pengfei Song; Hongling Li (Biochemical Genetics, 2026)

Reaction mechanisms and catalyst design principles of MOFs and their derivatives in the electrocatalytic nitrate reduction for ammonia production - Huaiyu Zhou; Qing Wang; Yan Pan; Shuo Pan; Da Cui; Jingru Bai (Journal of Environmental Chemical Engineering, 2026)

Degradation effects and mechanism of o-chlorotoluene by Raoultella planticola and Escherichia fergusonii - Pan Ye; Da-Mao Xu; Qing-Jun Meng; En-Wei Cao; Xue-Qiang Zhu (Journal of Environmental Chemical Engineering, 2026)

Divergent roles of phospholipids and triacylglycerol in flavor formation and trimethylamine generation in Antarctic krill oil - Gui-Mei Dong; Xue-Chen Pei; Wei-Cong Pan; Qian Wang; Fa-Wen Yin; Lei Qin; Da-Yong Zhou (Food Chemistry, 2026)

The effects and mechanisms of corn zein hydrolysate on intestinal inflammation in mouse and organoid models - Kangkai Chen; Ping Liu; Zirui Wang; Hui Xia; Ligang Yang; Da Pan; Guiju Sun; Wang Liao (Food Bioscience, 2026)

Biogeographic Barriers and Historic Climate Shape the Genetic Structure and Demography of the Freshwater Crab (Brachyura, Potamidae) in Continental‐Island Systems - Ruxiao Wang; Meijun Liu; Ruyi Jin; Boyang Shi; Hongying Sun; Da Pan (Zoologica Scripta, 2026)
Island biogeography provides a crucial framework for interpreting global biodiversity patterns; however, the distinctive dynamics of continental islands remain underexplored relative to those of volcanic oceanic islands. This knowledge gap obscures our understanding of species dispersal and evolution, particularly on small continental islands whose connectivity has been modulated by Quaternary sea‐level oscillations. Here, we integrate double‐digest restriction‐site‐associated DNA (ddRAD) sequencing with mitochondrial COI and 16S rRNA data to investigate the phylogeography, population structure, demographic history and ecological niche of the narrowly distributed freshwater crab Nanhaipotamon nanriense inhabiting mainland and nearby islands in southeastern China. Our analyses revealed strong genetic differentiation, highlighting a deeply divergent island lineage isolated by a narrow marine channel and an inland lineage isolated by the Minjiang River. Demographic reconstructions indicated significant population expansions during lower sea level in the Pleistocene, followed by population contractions correlated strongly with post‐glacial sea level rise in the Holocene. By synthesising genomic, demographic and ecological evidence, our study demonstrates how marine inundation, riverine barriers and glacio‐eustatic cycles jointly shape the genetic and distributional patterns of continental island freshwater species and also provide critical insights for conservation strategies.

Feature-enhanced hybrid-optimized convolutional neural network–long short-term memory framework for real-time early warning of sudden total suspended solids pollution events in riverine waters - Lijun Liu; Jingming Hou; Tian Wang; Guangzhao Chen; Guangxue Luan; Xinxin Pan; Da Liu (Journal of Environmental Management, 2026)

Reduction of Masseter Muscle Prominence After Treatment With OnabotulinumtoxinA: Results From a Phase 3 Double-Blind, Randomized, Placebo-Controlled Study Period in Europe - Juan García-Gavín; Rodrigo Da Mota; Dario Bertossi; Martina Kerscher; Radina Denkova; René Hopfinger; Reva McCaskill; Grace Pan; Catherine Foley; Helena Pavicic (Toxicon, 2026)

Isolation, purification, and functional characterization of porcine fibroblasts across different ages and anatomical sites for cultured meat - Wei Li; Chunyan Da; Moru Deng; Shijie Ding; Shuyu Pan; Xinyue Liang; Chunbao Li; Guanghong Zhou; Changbo Tang (Food Research International, 2026)

Monodisperse lutetium-177-labeled poly(lactic acid) microspheres for radioembolization therapy of hepatocellular carcinoma - Qing-Rong Jiang; Ping He; Ling-Yun Guo; Qi-Yi Mo; Xing-Long Zhou; Wei Wang; Zhuang Liu; Rui Xie; Da-Wei Pan; Wen-Jie Zhang; Xiao-Jie Ju; Liang-Yin Chu (Chemical Engineering Journal, 2026)

High-performance composite solid electrolyte with elevated ionic liquid and high-dielectric high-entropy oxide in poly(vinylidene fluoride-co-hexafluoropropylene) for advanced lithium-ion batteries - Wen-Hsuan Lu; Yen-Shuo Huang; Yen-Lin Chen; Yi-Hsuan Tseng; Jue-Hua Pan; You-Yi Li; Ying-Da Luo; Chun-Han Kuo; Chih-Ping Tan; Ruey-An Doong; Ho-Hsiu Chou; Ai-Yin Wang; et al. (Chemical Engineering Journal, 2026)

Polycrystalline ferroelectricity in a molecular crystal for piezoelectric sensing - Gele Teri; Jing-Song Tang; Peng-Cheng Zhuge; Jia-Qi Luo; Hao-Fei Ni; Lei Pan; Qiang-Qiang Jia; Yi Zhang; Da-Wei Fu; Zhi-Xu Zhang (Chemical Engineering Journal, 2026)

Clinical Evidence on the Health Benefits and Safety of Probiotic Lacticaseibacillus rhamnosus: A Systematic Review - Yu Yang; Jing Sui; Wang Liao; Shaokang Wang; Da Pan; Guiju Sun; Peng Gao; Xuesong Xiang; Hui Xia (Probiotics and Antimicrobial Proteins, 2026)

First evidence of CP violation in beauty baryon to charmonium decays - R. Aaij; A.S.W. Abdelmotteleb; C. Abellan Beteta; F. Abudinén; T. Ackernley; A.A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C.A. Aidala; Z. Ajaltouni; et al. (Science Bulletin, 2026)

WABAD : A world annotated bird acoustic dataset for passive acoustic monitoring - Cristian Pérez‐Granados; Jon Morant; Kevin F. A. Darras; Oscar H. Marín‐Gómez; Irene Mendoza; Miguel A. Muñoz‐Mohedano; Eduardo Santamaría‐García; Giulia Bastianelli; Alba Márquez‐Rodríguez; Michał Budka; Gerard Bota; José M. De la Peña‐Rubio; et al. (Ecology, 2026)
Under the current global biodiversity crisis, there is a need for automated and noninvasive monitoring techniques that can gather large amounts of data cost‐effectively at various ecological scales, from local to large spatial scales. These data can then be analyzed to inform stakeholders and decision‐makers. One such technique is passive acoustic monitoring, which is commonly coupled with automatic identification of animal species based on their sound. Automated sound analyses usually require the training of sound detection and identification algorithms. These algorithms are based on annotated acoustic datasets which mark the occurrence of sounds of species inside sound recordings. However, compiling large annotated acoustic datasets is time‐consuming and requires experts, and therefore, they normally cover reduced spatial, temporal, and taxonomic scales. This data paper presents WABAD, the World Annotated Bird Acoustic Dataset for passive acoustic monitoring. WABAD is designed to provide the public, the research community, and conservation managers with a novel and globally representative annotated acoustic dataset. This database includes 5047 min of audio files annotated to species‐level by local experts with the start and end time and the upper and lower frequencies of each identified bird vocalization in the recordings. The database has a wide taxonomic and spatial coverage, including information on 91,931 vocalizations from 1192 bird species recorded at 72 recording sites in 29 recording locations (mainly countries) and distributed across 13 biomes. WABAD can be used, for example, for developing and/or validating automatic species detection algorithms, answering ecological questions, such as assessing geographical variations on bird vocalizations, or comparing acoustic diversity indices with species‐based diversity indices. The dataset is published under a Creative Commons Attribution 4.0 International license that permits redistribution and reuse on the condition that the original work is properly credited.

Long-term community monitoring of volatile organic compounds and methane in Erie, Colorado: sources and health risks - Seong-Joon Kim; I-Ting Ku; Yong Zhou; Da Pan; Lena Low; Morgan Frazier; Brent Buck; Jeffrey L. Collett (Science of The Total Environment, 2026)

Cost-Effective rhamnolipids production from corn Bran and their application in essential oil extraction - Juliana P. Marques Teixeira; Gabriela Dornelas Marques; Michel Pedro Batista; Karen Stefany Conceição; Thaísa Maria da Roda Lino; Natalia Belebecha Terezo; Cesar Augusto Tischer; Alexandre Orsato; Gerson Nakazato; Nicole Caldas Pan; Josiane A. Vignoli; Doumit Camilios-Neto (World Journal of Microbiology and Biotechnology, 2026)

The Combination of Sodium Tanshinone IIA Sulfonate and Mesenchymal Stem Cell-derived Exosomes Against Spinal Cord Injury via VEGF Pathway - Dan Luo; Lin Ma; Zhijian Pan; Ling Chen; Zhifeng Hu; Chaolun Liang; Zenglu Wang; Zhifeng Xiao; Dingkun Lin; Jinfeng Li; Da Guo; Xing Li (Molecular Neurobiology, 2026)

Dual-mechanism defect engineering of multi-enzyme embedded ZIF-8 for efficient anthocyanin extraction from black rice - Mengyuan Cao; Bicong Wang; Yuchao Deng; Da-Wei Pan; Xiao-Jie Ju; Rui Xie; Zhuang Liu; Xing-Long Zhou; Mao-Jie Zhang; Wei Wang; Liang-Yin Chu (Chemical Engineering Journal, 2025)

Arthroderma guizhouense sp. nov., a Novel Geophilic Species from Guizhou, China - Kai-Rong Wang; Heng Pan; Bing-Da Sun; Gang Tao; Zhi-Yuan Zhang (Mycopathologia, 2025)

Corrigendum to “Immunological characteristics of the recombinant pseudorabies virus with chimeric PCV Cap protein in pigs” [Vet. Microbiol. 305 (2025) 110529] - Chenhe Lu; Wenjing Chen; Heng Chen; Gang Xing; Jiayu Ma; Hui Zhou; Linglong Qin; Da Liu; Shiping Sun; Peng Peng; Haimin Li; Yulan Jin; et al. (Veterinary Microbiology, 2025)

Spatiotemporal variations and risks assessment of PAH-bound suspended particles across different Asian countries: Insights from multi-city sampling and source apportionment - Kai Hsien Chi; Yen-Shun Hsu; Sheng-Lun Lin; Charles C.-K Chou; Somporn Chantara; Sereeter Lodoisamba; Thi Tuyet-Hanh Tran; Delgerzul Lodoisamba; Yuan Cheng Hsu; Chih-Da Wu; Tuan Hung Ngo; Shih Yu Pan (Environmental Research, 2025)

Reducing toxicity of atrazine using subcritical hydrolysis technology and investigation the hydrolysis mechanism - Shuo Pan; Huaiyu Zhou; Shuang Wu; Qing Wang; Jingru Bai; Da Cui; Junting Su (Environmental Science and Pollution Research, 2025)

Study on the role and function of RRS1 in cutaneous squamous cell carcinoma - Zhan-Yan Pan; Zhi-Nan Shi; Qiong Wu; Ting-Ting Hu; Xiao-Hui Mo; Da-Ke Dong; Qiang Ju (Tissue and Cell, 2025)

OsSPT38 encodes a novel SUMO E3 ligase that improves rice stress resilience and grain yield - Zi-Sheng Zhang; Zheng-Yi Zhang; Jin-Qiu Xia; Si-Yan Chen; Liang-Qi Sun; Jie Wu; Da-Yu He; Jing-Xian Wang; Qin-Yu Liang; Lei Wang; Ke Ruan; Tian Sang; et al. (Molecular Plant, 2025)

Gut-brain axis dysfunction mediates neurotoxicity of embryonic p-phenylenediamine exposure in zebrafish - Minyan Xu; Dongliang Pan; Jia Yi; Yi Zheng; Guoming Zeng; Jian Lin; Yang Song; Da Sun; Jiangfei Chen (Journal of Hazardous Materials, 2025)

Exploring the moisture absorption behaviours of microwave-processed wheat starch-stearic acid complexes from a molecular view - Tingting Gao; You Tian; Fei Pan; Da-Wen Sun (Food Chemistry, 2025)

Current status and research progress of sugarcane stem borers management - Jin-Da Wang; Huan-Tai Lin; Xian-Kun Shang; Hong-Li Shan; Ji-Hu Li; Xue-Hong Pan; Jiong Yin; Cheng-Wu Zou; Bao-Shan Chen; San-Ji Gao (European Journal of Agronomy, 2025)

Immunological characteristics of the recombinant pseudorabies virus with chimeric PCV Cap protein in pigs - Chenhe Lu; Wenjing Chen; Heng Chen; Gang Xing; Jiayu Ma; Hui Zhou; Linglong Qin; Liu Da; Shiping Sun; Peng Peng; Haimin Li; Yulan Jin; et al. (Veterinary Microbiology, 2025)

Uptake, translocation, and biotransformation of phthalate acid esters in crop plants: A comprehensive review - Nai-Xian Feng; Bogui Pan; Hong-Jia Huang; Yi-Tong Huang; Hui Lyu; Lei Xiang; Hai-Ming Zhao; Bai-Lin Liu; Yan-Wen Li; Quan-Ying Cai; Da-Wei Li; Ce-Hui Mo (Journal of Hazardous Materials, 2025)

Three-Dimensional Shallow P-wave Velocity Distribution in the Source Area of the 2021 MS6.0 Luxian Earthquake from Dense Array Seismic Imaging - Jian-xun Yang; Qi-yan Yang; Da-hu Li; Yong-ming Lu; Ping-ping Wu; Hui-li Guo; Ning-bo Jiang; Mi Gao; Heng Pan (Applied Geophysics, 2025)

Study of D s 1 ( 2460 ) + → D s + π + π - in B → D ‾ ( * ) D s + π + π - decays - R. Aaij; A.S.W. Abdelmotteleb; C.Abellan Beteta; F. Abudinén; T. Ackernley; A.A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C.A. Aidala; Z. Ajaltouni; et al. (Science Bulletin, 2025)

Electron delocalization-modulated hydroxyl binding for enhanced hydrogen evolution reaction activity - Da Liu; Peifang Guo; Qiangqiang Wang; Jin Zhou; Mingchang Zhang; Xingyu Ding; Chao Zheng; Hongge Pan; Renbing Wu (Science Bulletin, 2025)

Dynamic covalent synthesis of highly-crystalline and fully-cyclized aromatic COF as an artificial interphase layer toward stable lithium metal batteries - Wei Shao; Da Xu; Tiantian Wang; Huanghao Pan; Ying Liu; Xue Gao; Jiahuan Luo; Jing Wang; Zhong-Kun Li; Yao Guo; Huihui Zhao; Ning Fu; et al. (Chemical Engineering Journal, 2025)

Assessment of high-position glacial valleys in Southeast Tibet, China: an integrated approach using remote sensing, UAV, field investigation, and numerical simulation - Congyan Ran; Shishu Zhang; Xinfu Xing; Haizhu Qu; Zhanglei Wu; Da Zheng; Zhenhui Pan; Maohong Yao; Kai Zhang (Natural Hazards, 2025)

Proximity to petrochemical industry and risk of childhood asthma occurrence - Shih-Chun Pan; Wei-Shan Chin; Ching-Chun Huang; Yu-Cheng Chen; Chih-Da Wu; Chin-Yu Hsu; Pinpin Lin; Pau-Chung Chen; Yue Leon Guo (International Journal of Hygiene and Environmental Health, 2025)

Paleoclimate Fluctuations Facilitate the Biogeographical History of Endemic Species of Freshwater Crabs in China via Cycles of Introgressive Hybridisation and Habitat Isolation - Boyang Shi; Ruxiao Wang; Danhong Song; Juanjuan Xu; Lin Zhu; Yufang Sun; Rui Hu; Neil Cumberlidge; Da Pan; Hongying Sun (Journal of Biogeography, 2025)
Aim The impact of Pleistocene climate fluctuations on the biogeographical history of aquatic species has been a topic of enduring debate. This issue poses particular challenges for parapatric closely related species, especially those situated in transition zones where species assemblages occur between distinct zoogeographic boundaries. Location Eastern China. Taxon Five closely related Sinopotamon species and subspecies, S. shensiense , S. honanense , S. y. yangtsekiense , S. y. shanxianense , and S. y. tongbaiense . Methods These parapatric Sinopotamon species and subspecies, distributed along the boundary between the Palaearctic and Oriental realms in eastern China, offer an ideal model for addressing these challenges. We explored the biogeographic history of these species by conducting a comparative phylogeographic analysis using nine microsatellite loci and two mitochondrial DNA sequences, combined with morphological variation and fine‐tuned ecological niche modelling. Results Our phylogeographic analyses consistently revealed two well‐supported clades: clade A, for S. y. yangtsekiense , and clade B, which includes other species showing polyphyletic patterning and significant gene introgression. The Nanyang Basin and surrounding mountains regions (NBSM) was identified as a critical shared refuge and hybrid zone, facilitating interspecific introgression through at least two putative hybridisation events. During the Late Pleistocene glacial cycles, introgressive hybridisation of these species occurred in the NBSM, followed by rapid expansion and colonisation of heterogenous habitats during interglacial cycles, with dispersal corridors largely aligning with the local river system. In particular, the diffusion corridor of S. honanense significantly disrupted the continuous distribution of S. y. shanxianense and S. y. tongbaiense , indicating that S. honanense has replaced S. y. shanxianense and S. y. tongbaiense in the NYSM and caused a disruption in its distribution. Main Conclusions The biogeographic histories of the species in clade B are consistent with a mixing–isolation–mixing model, which suggests that populations experienced repeated introgressive hybridisation during glacial periods and regional habitat isolation during interglacial periods. Our findings represent a classic case of fine tracking biogeographical scenarios in parapatric species and provide unprecedented insights into the evolutionary radiation of the freshwater fauna that occupies zoogeographic boundaries.

Highly cost-effective wheat starch-stearic acid complexes enabled by microwave processing: Structural properties, anti-digestion, and molecular dynamics simulation - Tingting Gao; Da-Wen Sun; You Tian; Ji Ma; Fei Pan (Food Chemistry, 2025)

Ferric ammonium citrate regulates iron death in mature porcine oocytes and their embryonic development in vitro through the NRF2 signaling pathway - Da Xu; Caifei Li; Yao Huang; Kaixin Hu; Cheng Wang; Pengyang Zhou; Haiying Shen; Chang Liu; Jiatong Xu; Jinyuan He; Jiaxu Jiang; Qi Qi; et al. (Theriogenology, 2025)

Metal/organic interface carrier quenching suppression for stable and efficient near-infrared quantum dot light-emitting diodes - Wan-Shan Shen; Yang Liu; Xingtong Chen; Hong-Wei Duan; Jia-Lin Pan; Zhong-Da Zhang; Feng Zhao; Zeke Liu; Sui-Dong Wang; Wanli Ma; Song Chen; Ya-Kun Wang; et al. (Chemical Engineering Journal, 2025)

Phylogenomic analysis of brachyuran crabs using transcriptome data reveals possible sources of conflicting phylogenetic relationships within the group - Da Pan; Yunlong Sun; Boyang Shi; Ruxiao Wang; Peter K.L. Ng; Danièle Guinot; Neil Cumberlidge; Hongying Sun (Molecular Phylogenetics and Evolution, 2024)

Organic matter excreted by the protozoan Tetrahymena thermophila and its effects on the bioaccumulation of nanoparticles - Ke-Da Zhang; Hong-Jie Zhang; Jun-Long Song; Xin-Lei Wang; Wei Pan; Mei Wang; Bin Huang; Liuyan Yang; Ai-Jun Miao (Journal of Hazardous Materials, 2024)

Combination and summary of ATLAS dark matter searches interpreted in a 2HDM with a pseudo-scalar mediator using 139 fb−1 of s = 13 TeV pp collision data - G. Aad; B. Abbott; K. Abeling; N.J. Abicht; S.H. Abidi; A. Aboulhorma; H. Abramowicz; H. Abreu; Y. Abulaiti; A.C. Abusleme Hoffman; B.S. Acharya; C. Adam Bourdarios; et al. (Science Bulletin, 2024)

Gut antibiotic resistome during pregnancy associates with the risk of gestational diabetes mellitus: New evidence from a prospective nested case−control study - Jing Li; Zhonghan Sun; Fengjiang Sun; Yuwei Lai; Xinzhu Yi; Zhang Wang; Jiaying Yuan; Yayi Hu; An Pan; Xiong-Fei Pan; Yan Zheng; Da Chen (Journal of Hazardous Materials, 2024)

Prediction of freezing point and moisture distribution of beef with dual freeze-thaw cycles using hyperspectral imaging - Qingyi Wei; Chaoying Pan; Hongbin Pu; Da-Wen Sun; Xiaolei Shen; Zhe Wang (Food Chemistry, 2024)

High-throughput generation of monodisperse double emulsions via controllable symmetric splitting in Y-shaped microchannels - Lin-Ling Fan; Wei Wang; Xiao-Jie Ju; Zhuang Liu; Rui Xie; Jianhong Xu; Guangsheng Luo; Da-Wei Pan; Liang-Yin Chu (Chemical Engineering Journal, 2024)

Dialdehyde starch cross-linked aminated gelatin sponges with excellent hemostatic performance and biocompatibility - Yu-He Zhu; Chen-Yu Zhou; Xu Peng; Wei Wang; Zhuang Liu; Rui Xie; Da-Wei Pan; Xiao-Jie Ju; Liang-Yin Chu (Carbohydrate Polymers, 2024)

Rotavirus infection inhibits SLA-I expression on the cell surface by degrading β2 M via ERAD-proteasome pathway - Zhaoyang Jing; Ling Wu; Yudi Pan; Liaoyuan Zhang; Xin Zhang; Da Shi; Hongyan Shi; Jianfei Chen; Zhaoyang Ji; Jiyu Zhang; Tingshuai Feng; Jin Tian; et al. (Veterinary Microbiology, 2024)

Tailoring raloxifene into single-component molecular crystals possessing multilevel stimuli-responsive room-temperature phosphorescence - Zhichao Pan; Jinming Song; Shasha Zhang; Ping Zeng; Ju Mei; Da-Hui Qu (Science Bulletin, 2024)

Cell-excreted proteins mediate the interactions of differently sized silica nanoparticles during cellular uptake - Bin Huang; Jia-Ming Li; Xiao-Mei Zang; Mei Wang; Wei Pan; Ke-Da Zhang; Huan He; Qiao-Guo Tan; Ai-Jun Miao (Journal of Hazardous Materials, 2024)

Role of probiotics/synbiotic supplementation in glycemic control: A critical umbrella review of meta-analyses of randomized controlled trials - Dengfeng Xu; Lingmeng Fu; Da Pan; YiFang Chu; Meiyuan Feng; Yifei Lu; Chao Yang; Yuanyuan Wang; Jiayue Xia; Guiju Sun (Critical Reviews in Food Science and Nutrition, 2024)

Do greenness and landscape indices for greenspace correlate with suicide ratio? - Hsiao-Yun Lee; Hao-Ting Chang; Samuel Herianto; Chi-Shin Wu; Wan-Yu Liu; Chia-Pin Yu; Wen-Chi Pan; Chih-Da Wu (Landscape and Urban Planning, 2024)

Diversification of freshwater crabs on the sky islands in the Hengduan Mountains Region, China - Bo-Yang Shi; Da Pan; Kang-Qin Zhang; Tian-Yu Gu; Darren C.J. Yeo; Peter K.L. Ng; Neil Cumberlidge; Hong-Ying Sun (Molecular Phylogenetics and Evolution, 2024)

Chloroxylenol positively affects the aerobic sequencing batch reactor performance and reshapes microbial communities and antibiotic resistance genes - Qiao Ma; Hanqing Pan; Da Li; Jingwei Wang (Journal of Water Process Engineering, 2024)

Construction of Rh-N4 single atoms and Rh clusters dual-active sites for synergistic heterogeneous hydroformylation of olefins with ultra-high turnover frequency - Da Yang; Shu Tao; Houyu Zhu; Zhidong Wang; Wenwen Gao; Jinggang Yu; Minmin Wang; Guangxun Sun; Junxi Li; Hsiao-Chien Chen; Bin Liu; Yongming Chai; et al. (Chemical Engineering Journal, 2024)

Air quality impacts from the development of unconventional oil and gas well pads: Air toxics and other volatile organic compounds - I-Ting Ku; Yong Zhou; Arsineh Hecobian; Katherine Benedict; Brent Buck; Emily Lachenmayer; Bryan Terry; Morgan Frazier; Jie Zhang; Da Pan; Lena Low; Amy Sullivan; et al. (Atmospheric Environment, 2024)

Toxic vascular effects of polystyrene microplastic exposure - Jianlong Yan; Yanbin Pan; Junbo He; Xinli Pang; Wenming Shao; Caiping Wang; Rongning Wang; Yaqiong He; Min Zhang; Juheng Ye; Chaolan Lin; Feng Lin; et al. (Science of The Total Environment, 2023)

Anti-freezing hydrogel thermocells with confined microcrystallization for enhanced low-grade heat harvest - Ping-Fan Li; Ting-Yuan Hu; Tao Luo; Zhuang Liu; Xiao-Jie Ju; Rui Xie; Da-Wei Pan; Wei Wang; Liang-Yin Chu (Chemical Engineering Journal, 2023)

Hydrothermal carbonization of food waste for sustainable biofuel production: Advancements, challenges, and future prospects - Shuang Wu; Qing Wang; Minghui Fang; Dongyang Wu; Da Cui; Shuo Pan; Jingru Bai; Faxing Xu; Zhenye Wang (Science of The Total Environment, 2023)

C-doped ZnO nanocomposites molecularly imprinted photoelectrochemical sensor for ultrasensitive and selective detection of oxytetracycline in milk - Huafang Zhang; Qinghong Pan; Wanying Cai; Xiaowei Shi; Da-Peng Yang; Hetong Lin; Enhui Qiu (Food Chemistry, 2023)

Determinants of residential greenness and its association with prostate cancer risk: A case-control study in Singapore - Yueh Jia Lee; Wei Qi Loh; Trung Kien Dang; Cecilia Woon Chien Teng; Wen-Chi Pan; Chih-Da Wu; Sin Eng Chia; Wei Jie Seow (Environmental Research, 2023)

Exposure to per- and polyfluoroalkyl substances in women with twin pregnancies: Patterns and variability, transplacental transfer, and predictors - Songyi Huang; Xiaojie Li; Langjing Deng; Jinying Xie; Guangtong Huang; Chenyan Zeng; Nanxin Wu; Sui Zhu; Chaoqun Liu; Hong Mei; Han Xiao; Da Chen; et al. (Journal of Hazardous Materials, 2023)

Microbial communities and their correlation with flavor compound formation during the mechanized production of light-flavor Baijiu - Lu-Jun Luo; Liang Song; Ying Han; Pan Zhen; Da-Yong Han; Xin Zhao; Xin Zhou; Yu-Hua Wei; Hui-Xin Yu; Pei-Jie Han; Feng-Yan Bai (Food Research International, 2023)

Occupant behavior modules development for coupled simulation in DeST 3.0 - Xiaoyu Jia; Yiqun Pan; Mingya Zhu; Han Zhu; Zhengrong Li; Jingsi Zhang; Xiang Zhou; Song Pan; Chuang Wang; Da Yan; Zejun Wu; Huiyan Deng; et al. (Energy and Buildings, 2023)

Sustainable route to prepare functional lignin-containing cellulose nanofibrils - Kexia Jin; Da Zhang; Binqiang Pan; Khak Ho Lim; Tiffany Abitbol; Wen-Jun Wang; Xuan Yang (Chemical Engineering Journal, 2023)

The culprit for the declining performance of anaerobic reactors caused by calcification: Bioavailability deterioration - Wenda Chen; Huiming Tang; Dongdong Xu; Wenji Li; Chao Pan; Leiyan Guo; Da Kang; Ping Zheng; Meng Zhang (Bioresource Technology, 2023)

Ecological distribution of anaerobic granular sludge towards efficient anaerobic reactor - Wenda Chen; Huiming Tang; Dongdong Xu; Wenji Li; Chao Pan; Leiyan Guo; Da Kang; Baolan Hu; Ping Zheng; Meng Zhang (Bioresource Technology, 2023)

Multiple Palaeozoic–Mesozoic orogenic events in the SE Yangtze Block, China: evidence from the petrogenesis and deformation of gneissic granites from the Nanwenhe metamorphic dome and regional correlation analysis - Xinming Zhang; Da Zhang; Jinbo Pan; Minfeng Bi; Ganguo Wu; Xiaolong He; Bojie Hu; Chaoyang Que; Yongjun Di; Wei Xue (International Geology Review, 2023)

A life-threatening bleeding prediction model for immune thrombocytopenia based on personalized machine learning: a nationwide prospective cohort study - Zhuo-Yu An; Ye-Jun Wu; Yu Hou; Heng Mei; Wei-Xia Nong; Wen-Qian Li; Hu Zhou; Ru Feng; Jian-Ping Shen; Jun Peng; Hai Zhou; Yi Liu; et al. (Science Bulletin, 2023)

Estimating the daily average concentration variations of PCDD/Fs in Taiwan using a novel Geo-AI based ensemble mixed spatial model - Chin-Yu Hsu; Tien-Wei Lin; Jennieveive B. Babaan; Aji Kusumaning Asri; Pei-Yi Wong; Kai-Hsien Chi; Tuan Hung Ngo; Yu-Hsuan Yang; Wen-Chi Pan; Chih-Da Wu (Journal of Hazardous Materials, 2023)

Surface solid frustrated Lewis pair constructed on alumina for selective hydrogenation reaction - Zhaowei Tian; Lei Wang; Tianyao Shen; Pan Yin; Weimin Da; Zhitong Qian; Xun Zhao; Guirong Wang; Yusen Yang; Min Wei (Chemical Engineering Journal, 2023)

Towards intensified preservation technology of anammox granular sludge: Insights into the role of energy support - Chao Pan; Wenji Li; Dongdong Xu; Wenda Chen; Leiyan Guo; Da Kang; Baolan Hu; Ping Zheng; Meng Zhang (Chemical Engineering Journal, 2023)

Characterization of sandalwood (E,E)-α-farnesene synthase whose overexpression enhances cold tolerance through jasmonic acid biosynthesis and signaling in Arabidopsis - Xinhua Zhang; Xiaohong Chen; Jaime A. Teixeira da Silva; Ting Zhang; Yuping Xiong; Yuan Li; Yunfei Yuan; Xiaoping Pan; Guohua Ma (Planta, 2023)

High quality diet attenuated the positive association between polychlorinated biphenyls and premature mortality among middle-aged and older adults - Weigui Ni; Qingping Xue; Shanshan Zhang; Xue Yang; Shiyi Wu; Xingchen He; Yan Xiao; Wenling Chang; Ying Wen; Yichao Huang; Yi-Xin Wang; Da Chen; et al. (Environmental Research, 2023)

Phthalate exposure with sperm quality among healthy Chinese male adults: The role of sperm cellular function - Pan Yang; Lang-Jing Deng; Jin-Ying Xie; Xiao-Jie Li; Xiao-Na Wang; Bin Sun; Tian-Qing Meng; Cheng-Liang Xiong; Yi-Chao Huang; Yi-Xin Wang; An Pan; Da Chen; et al. (Environmental Pollution, 2023)

Two new diterpenoids from the rhizomes of Zingiber officinale - Mi Zhou; Ting Li; Chen Zeng; Da-bo Pan; Hai-bo Li; Yang Yu (Natural Product Research, 2023)

Water quality determines protist taxonomic and functional group composition in a high-altitude wetland of international importance - Ruizhi An; Yang Liu; Chengmei Pan; Zhen Da; Peng Zhang; Nanqian Qiao; Feng Zhao; Sang Ba (Science of The Total Environment, 2023)

Beta diversity of urban spontaneous plants and its drivers in 9 major cities of Yunnan province, China - Zhiwen Gao; Yingji Pan; Peter M. Van Bodegom; Ellen Cieraad; Dingliang Xing; Yanyi Yang; Tiyuan Xia; Xinyi Luo; Kun Song; Liangjun Da; Dan Malkinson (Landscape and Urban Planning, 2023)

Information sharing for competing manufacturers: The strategic analysis of environmental innovation - Pan Zhang; Da Zhao; Zhi Qiao; Yu Xiong; Jiamin Liang (Journal of Cleaner Production, 2023)

Transcatheter closure of perimembranous ventricular septal defect using a novel fully bioabsorbable occluder: multicenter randomized controlled trial - Shouzheng Wang; Zefu Li; Yunbing Wang; Tianli Zhao; Xuming Mo; Taibing Fan; Jianhua Li; Tao You; Rundi Deng; Wenbin Ouyang; Weiwei Wang; Chuangnian Zhang; et al. (Science Bulletin, 2023)

Ultrasensitive hydrogel grating detector for real-time continuous-flow detection of trace threat Pb2+ - Xiao-Yu Tian; Meng-Wei Sun; Guo-Yu Wen; Min Cao; Da-Wei Pan; Rui Xie; Xiao-Jie Ju; Zhuang Liu; Wei Wang; Liang-Yin Chu (Journal of Hazardous Materials, 2023)

Residential greenness and air pollution's association with nasal microbiota among asthmatic children - Aji Kusumaning Asri; Tsunglin Liu; Hui-Ju Tsai; Hsiao-Yun Lee; Wen-Chi Pan; Chih-Da Wu; Jiu-Yao Wang (Environmental Research, 2023)

Holdup of sub-granules towards enhanced production of anammox sludge in a dual circulation sludge bed reactor - Dongdong Xu; Wenda Chen; Chao Pan; Wenji Li; Leiyan Guo; Da Kang; Ping Zheng; Baolan Hu; Meng Zhang (Chemical Engineering Journal, 2023)

Co-exposure to phenols and phthalates during pregnancy with the difference of body size in twins at one month old - Hong Mei; Langjing Deng; Jinying Xie; Xiaojie Li; Nanxin Wu; Liqin Hu; Guangtong Huang; Fanyu Mo; Da Chen; Han Xiao; Pan Yang (Chemosphere, 2023)

Microfluidic emulsification techniques for controllable emulsion production and functional microparticle synthesis - Wei Wang; Bing-Yu Li; Mao-Jie Zhang; Yao-Yao Su; Da-Wei Pan; Zhuang Liu; Xiao-Jie Ju; Rui Xie; Yousef Faraj; Liang-Yin Chu (Chemical Engineering Journal, 2023)

Boundary effect of toppling failure based on three-dimensional mechanical model - Jun-chao Cai; Da Zheng; Neng-pan Ju; Run-qiu Huang; Wei-hua Zhao (Journal of Mountain Science, 2022)

Evaluating the survival of Aspergillus niger in a highly polluted red soil with addition of Phosphogypsum and bioorganic fertilizer - Lingzi Meng; Shang Pan; Limin Zhou; Choochad Santasup; Mu Su; Da Tian; Zhen Li (Environmental Science and Pollution Research, 2022)

Risk of thyroid cancer and benign nodules associated with exposure to parabens among Chinese adults in Wuhan, China - Nan-Xin Wu; Lang-Jing Deng; Feng Xiong; Jin-Ying Xie; Xiao-Jie Li; Qiang Zeng; Jia-Chen Sun; Da Chen; Pan Yang (Environmental Science and Pollution Research, 2022)

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

Magnetotactic bacteria in vertical sediments of volcanic lakes in NE China appear Alphaproteobacteria dominated distribution regardless of waterbody types - Tao Liu; Huiyun Da; Shuang Zhang; Weidong Wang; Hong Pan; Lei Yan (World Journal of Microbiology and Biotechnology, 2022)

Effect of Chromium Supplementation on Blood Glucose and Lipid Levels in Patients with Type 2 Diabetes Mellitus: a Systematic Review and Meta-analysis - Fengyi Zhao; Da Pan; Niannian Wang; Hui Xia; Hong Zhang; Shaokang Wang; Guiju Sun (Biological Trace Element Research, 2022)

Addressing alpine plant phylogeography using integrative distributional, demographic and coalescent modeling - Dennis J. Larsson; Da Pan; Gerald M. Schneeweiss (Alpine Botany, 2022)
Phylogeographic studies of alpine plants have evolved considerably in the last two decades from ad hoc interpretations of genetic data to statistical model-based approaches. In this review we outline the developments in alpine plant phylogeography focusing on the recent approach of integrative distributional, demographic and coalescent (iDDC) modeling. By integrating distributional data with spatially explicit demographic modeling and subsequent coalescent simulations, the history of alpine species can be inferred and long-standing hypotheses, such as species-specific responses to climate change or survival on nunataks during the last glacial maximum, can be efficiently tested as exemplified by available case studies. We also discuss future prospects and improvements of iDDC.

A new open‐path eddy covariance method for nitrous oxide and other trace gases that minimizes temperature corrections - Da Pan; Ilya Gelfand; Lei Tao; Michael Abraha; Kang Sun; Xuehui Guo; Jiquan Chen; G. Philip Robertson; Mark A. Zondlo (Global Change Biology, 2022)
Low‐power, open‐path gas sensors enable eddy covariance (EC) flux measurements in remote areas without line power. However, open‐path flux measurements are sensitive to fluctuations in air temperature, pressure, and humidity. Laser‐based, open‐path sensors with the needed sensitivity for trace gases like methane (CH 4 ) and nitrous oxide (N 2 O) are impacted by additional spectroscopic effects. Corrections for these effects, especially those related to temperature fluctuations, often exceed the flux of gases, leading to large uncertainties in the associated fluxes. For example, the density and spectroscopic corrections arising from temperature fluctuations can be one or two orders of magnitude greater than background N 2 O fluxes. Consequently, measuring background fluxes with laser‐based, open‐path sensors is extremely challenging, particularly for N 2 O and gases with similar high‐precision requirements. We demonstrate a new laser‐based, open‐path N 2 O sensor and a general approach applicable to other gases that minimizes temperature‐related corrections for EC flux measurements. The method identifies absorption lines with spectroscopic effects in the opposite direction of density effects from temperature and, thus, density and spectroscopic effects nearly cancel one another. The new open‐path N 2 O sensor was tested at a corn ( Zea mays L.) field in Southwestern Michigan, United States. The sensor had an optimal precision of 0.1 ppbv at 10 Hz and power consumption of 50 W. Field trials showed that temperature‐related corrections were 6% of density corrections, reducing EC random errors by 20‐fold compared to previously examined lines. Measured open‐path N 2 O EC fluxes showed excellent agreement with those made with static chambers ( m = 1.0 ± 0.3; r 2 = .96). More generally, we identified absorption lines for CO 2 and CH 4 flux measurements that can reduce the temperature‐related corrections by 10–100 times compared to existing open‐path sensors. The proposed method provides a new direction for future open‐path sensors, facilitating the expansion of accurate EC flux measurements.

Transcriptome Analysis Reveals Candidate Genes Involved in Anthocyanin Biosynthesis in Flowers of the Pagoda Tree (Sophora japonica L.) - Liping Guo; Jaime A. Teixeira da Silva; Qinghua Pan; Ting Liao; Xiaonan Yu (Journal of Plant Growth Regulation, 2022)

Relationship Between Selenium in Human Tissues and Breast Cancer: a Meta-analysis Based on Case-Control Studies - Xiaopan Zhu; Da Pan; Niannian Wang; Shaokang Wang; Guiju Sun (Biological Trace Element Research, 2021)

Three new cycloart-7-ene triterpenoid glycosides from Cimicifuga dahurica and their anti-inflammatory effects - Qian-Qian Pang; Yu-Dan Mei; Yuan-Chu Zhang; Ling-Xian Liu; Dan-Feng Shi; Da-Bo Pan; Xin-Sheng Yao; Hai-Bo Li; Yang Yu (Natural Product Research, 2021)

PrbP modulates biofilm formation in Liberibacter crescens - Lei Pan; Christopher L. Gardner; Reagan Beliakoff; Danilo da Silva; Ran Zuo; Fernando A. Pagliai; Kaylie A. Padgett‐Pagliai; Marcelo L. Merli; Erol Bahadiroglu; Claudio F. Gonzalez; Graciela L. Lorca (Environmental Microbiology, 2021)
Summary In Liberibacter asiaticus , PrbP is a transcriptional regulatory protein involved in survival and persistence during host infection. Tolfenamic acid was previously found to inhibit interactions between PrbP and the promotor region of rplK , resulting in reduced survival of L . asiaticus in the citrus host. In this study, we performed transcriptome analyses to elucidate the PrbP regulon in L . crescens , as it is phylogenetically the closest related species to L . asiaticus that can be grown in laboratory conditions. Chemical inhibition of PrbP with tolfenamic acid revealed that PrbP is involved in the regulation of diverse cellular processes, including stress response, cell motility, cell cycle and biofilm formation. In vitro DNA binding and bacterial two‐hybrid assays also suggested that PrbP is a global regulator of multiple transcription factors (RpoH, VisN, PleD, MucR, MocR and CtrA) at both transcriptional and/or post‐transcriptional levels. Sub‐lethal concentrations of tolfenamic acid significantly reduced the attachment of L . crescens during biofilm formation and decreased long‐term persistence in biofilm structures. Overall, our findings show the importance of PrbP in regulating diverse biological processes through direct and indirect interactions with other transcriptional regulators in L . crescens .

A new nitrogen-containing iridoid glycoside from lonicera macranthoides - Yu-Dan Mei; Hai-Bo Li; Ling-Xian Liu; Dan-feng Shi; Da-bo Pan; Xin-Sheng Yao; Yang Yu (Natural Product Research, 2021)

Effects of Copper Supplementation on Blood Lipid Level: a Systematic Review and a Meta-Analysis on Randomized Clinical Trials - Shaokang Wang; Niannian Wang; Da Pan; Hong Zhang; Guiju Sun (Biological Trace Element Research, 2021)

Inhibition of fruit softening by cold plasma treatments: affecting factors and applications - Ya-Wen Pan; Jun-Hu Cheng; Da-Wen Sun (Critical Reviews in Food Science and Nutrition, 2021)

Regional climates shape the biogeographic history of a broadly distributed freshwater crab species complex - Boyang Shi; Da Pan; Yufang Sun; Xiaorui Liu; Xiulin Lv; Neil Cumberlidge; Hongying Sun (Journal of Biogeography, 2021)
Aim The evolutionary importance of paleoclimate regimes has been noted in biogeographic studies. However, little is known about how paleoclimate differences shaped the biogeographic pattern and diversification history of the freshwater fauna in important zoogeographical boundary regions. Here, we aim to investigate how past regional climatic differences have shaped the biogeographic history of the inland aquatic fauna in China using an endemic freshwater crab species complex found on both sides of the Qinling Mountains–Huaihe River Line (QHL), a critical ecological boundary in eastern China, as a model system. Location Eastern China, the Qinling Mountains–Huaihe River Line. Taxon The Sinopotamon yangtsekiense species complex. Methods A total of 482 individuals of Sinopotamon yangtsekiense sensu lato were collected from 34 localities throughout its entire distributional range. The phylogeographic analyses of population structure, morphological and genetic variations, and demographic dynamics were made based on multiple mtDNA and nuDNA loci and on morphological traits. Fine‐tuned ecological niche modeling was used to reconstruct the location of climatically suitable areas that existed during the Last Glacial Maximum. Results The divergence of two freshwater crab lineages across the QHL correlated with significant past variations in monsoon intensity and with the location of multiple refuges. The divergence time was broadly consistent with the timing of the critical paleoclimate transition event in the mid‐Pleistocene (95% HPD, 0.48–1.06 Ma). Each freshwater crab lineage has evolved distinct male genital traits associated with their isolation in areas with different precipitation rates and temperatures in the past. The patterns of crab distribution observed today reflect past contractions of the two lineages in response to glacial and interglacial cycles during the Pleistocene, followed by their subsequent rapid expansion after the Last Glacial Maximum (~15 kya). Main conclusions Populations of the widespread species Sinopotamon yangtsekiense s.l. experienced a deep division in the past that led to the phylogeographical isolation observed today. The two main drivers of genetic isolation in this taxon were (a) differences in the intensity of the monsoons on each side of the QHL boundary during the mid‐Pleistocene, and (b) isolation of different populations of S. yangtsekiense s.l. in a number of separate refuges during the LGM.

An explicit test of Pleistocene survival in peripheral versus nunatak refugia in two high mountain plant species - Da Pan; Karl Hülber; Wolfgang Willner; Gerald M. Schneeweiss (Molecular Ecology, 2020)
Pleistocene climate fluctuations had profound influence on the biogeographical history of many biota. As large areas in high mountain ranges were covered by glaciers, biota were forced either to peripheral refugia (and possibly beyond to lowland refugia) or to interior refugia (nunataks). However, nunatak survival remains controversial as it relies solely on correlative genetic evidence. Here, we test hypotheses of glacial survival using two high alpine plant species (the insect‐pollinated Pedicularis asplenifolia and wind‐pollinated Carex fuliginosa ) in the European Alps. Employing the iDDC (integrative Distributional, Demographic and Coalescent) approach, which couples species distribution modelling, spatial and temporal demographic simulation and Approximate Bayesian Computation, we explicitly test three hypotheses of glacial survival: (a) peripheral survival only, (b) nunatak survival only and (c) peripheral plus nunatak survival. In P. asplenifolia the peripheral plus nunatak survival hypothesis was supported by Bayes factors (BF> 100), whereas in C. fuliginosa the peripheral survival only hypothesis, although best supported, could not be unambiguously distinguished from the peripheral plus nunatak survival hypothesis (BF = 5.58). These results are consistent with current habitat preferences ( P. asplenifolia extends to higher elevations) and the potential for genetic swamping (i.e., replacement of local genotypes via hybridization with immigrating genotypes [expected to be higher in the wind‐pollinated C. fuliginosa ]). Although the persistence of plants on nunataks during glacial periods has been debated and studied over decades, this is one of the first studies to explicitly test the hypothesis instead of solely using correlative evidence.

Rare variants in FANCA induce premature ovarian insufficiency - Xi Yang; Xiaojin Zhang; Jiao Jiao; Feng Zhang; Yuncheng Pan; Qiqi Wang; Qing Chen; Baozhu Cai; Shuyan Tang; Zixue Zhou; Siyuan Chen; Hao Yin; et al. (Human Genetics, 2019)
Premature ovarian insufficiency (POI) is a major cause of reduced female fertility and affects approximately 1% women under 40 years of age. Recent advances emphasize the genetic heterogeneity of POI. Fanconi anemia (FA) genes, traditionally known for their essential roles in DNA repair and cytogenetic instability, have been demonstrated to be involved in meiosis and germ cell development. Here, we conducted whole-exome sequencing (WES) in 50 Han Chinese female patients with POI. Rare missense variants were identified in FANCA ( Fanconi anemia complementation group A ): c.1772G > A (p.R591Q) and c.3887A > G (p.E1296G). Both variants are heterozygous in the patients and very rare in the human population. In vitro functional studies further demonstrated that these two missense variants of FANCA exhibited reduced protein expression levels compared with the wild type, suggesting the partial loss of function. Moreover, mono-ubiquitination levels of FANCD2 upon mitomycin C stimulation were significantly reduced in cells overexpressing FANCA variants. Furthermore, a loss-of-function mutation of Fanca was generated in C57BL/6 mice for in vivo functional assay. Consistently, heterozygous mutated female mice ( Fanca + / − ) showed reduced fertility and declined numbers of follicles with aging when compared with the wild-type female mice. Collectively, our results suggest that heterozygous pathogenic variants in FANCA are implicated in non-syndromic POI in Han Chinese women, provide new insights into the molecular mechanisms of POI and highlight the contribution of FANCA variants in female subfertility.

Mechanism of toppling and deformation in hard rock slope: a case of bank slope of Hydropower Station, Qinghai Province, China - Jun-chao Cai; Neng-pan Ju; Run-qiu Huang; Da Zheng; Wei-hua Zhao; Long-qi Li; Jian Huang (Journal of Mountain Science, 2019)

Determination of dietary nitrite in patients with esophageal pre-cancerous lesion and normal people: a duplicate diet study - Ting Zhang; Da Pan; Ming Su; Ling-Meng Fu; Cai-Yun Miao; Qing-Yang Yan; Jing Wang; Li-Gang Yang; Shao-Kang Wang; Gui-Ju Sun (Food Additives & Contaminants: Part A, 2018)

Molecular Identification and Genetic Diversity Analysis of Chinese Sugarcane (Saccharum spp. Hybrids) Varieties using SSR Markers - Ahmad Ali; Wang Jin-Da; Pan Yong-Bao; Deng Zu-Hu; Chen Zhi-Wei; Chen Ru-Kai; Gao San-Ji (Tropical Plant Biology, 2017)

Cryopreservation of grapevine (Vitis spp.)—a review - Wen-Lu Bi; Chen Pan; Xin-Yi Hao; Zhen-Hua Cui; Mafatlal M. Kher; Zvjezdana Marković; Qiao-Chun Wang; Jaime A. Teixeira da Silva (In Vitro Cellular & Developmental Biology - Plant, 2017)

Deletion of mammalian sterile 20-like kinase 1 attenuates neuronal loss and improves locomotor function in a mouse model of spinal cord trauma - Pan-feng Wang; Da-yuan Xu; Yuntong Zhang; Xiao-bin Liu; Yan Xia; Pan-yu Zhou; Qing-ge Fu; Shuo-gui Xu (Molecular and Cellular Biochemistry, 2017)

Study of a full-wave equation-based seismic illumination analysis - Wei Liu; Cheng Yin; Dawei Li; Da Peng; Shulin Pan (Arabian Journal of Geosciences, 2017)

Biodegradation of sulfamethazine by an isolated thermophile–Geobacillus sp. S-07 - Lan-jia Pan; Xiao-da Tang; Chun-xing Li; Guang-wei Yu; Yin Wang (World Journal of Microbiology and Biotechnology, 2017)

Variations and trends of trans-boundary runoff in the longitudinal range-gorge region - Yan-ling Yu; Feng Pan; Xin-you Liu; Wen-hua Chen; Da-ming He (Journal of Mountain Science, 2017)

Microsatellite records for volume 8, issue 4 - Alejandra Paola Ojeda; Alexandre Wagner Silva Hilsdorf; Ana Caroline Leite; Ao-ao Yang; Ayako Izuno; Chongbo He; Chun-ya Zhou; Daisuke Kyogoku; Danilo Caneppele; Dongmei Zhu; Fernando Stopato da Fonseca; Hao Yin; et al. (Conservation Genetics Resources, 2016)

Microsatellite records for volume 8, issue 3 - Yan-Ling Cao; Lívia Izabela Caputo; Hongyi Cheng; Fausto Moreira da Silva Carmo; Leiliane Campos de Carvalho; Gabriel de Menezes Yazbeck; Zélia de Oliveira Teixeira; Jiaxin Fu; José Antonio Guerrero; Guibing Hu; Jun Li; Zhihua Lin; et al. (Conservation Genetics Resources, 2016)

TDO as a therapeutic target in brain diseases - Cheng-Peng Yu; Ze-Zheng Pan; Da-Ya Luo (Metabolic Brain Disease, 2016)

Highly selective and efficient biotransformation of linarin to produce tilianin by naringinase - Pan Cui; Tong-Yi Dou; Shi-Yang Li; Jun-Xia Lu; Li-Wei Zou; Ping Wang; Yan-Ping Sun; Da-Cheng Hao; Guang-Bo Ge (Biotechnology Letters, 2016)

Balancing selection contributed to domestication of autopolyploid sugarcane (Saccharum officinarum L.) - Jie Arro; Jong-Won Park; Ching Man Wai; Robert VanBuren; Yong-Bao Pan; Chifumi Nagai; Jorge da Silva; Ray Ming (Euphytica, 2016)

Cyclic load testing of pre-stressed rock anchors for slope stabilization - Da Zheng; Fang-zhou Liu; Neng-pan Ju; J. David Frost; Run-qiu Huang (Journal of Mountain Science, 2016)

Identification of insecticidal constituents of the essential oils of Dahlia pinnata Cav. against Sitophilus zeamais and Sitophilus oryzae - Da-Cheng Wang; Da-Ren Qiu; Li-Na Shi; Hong-Yu Pan; Ya-Wei Li; Jin-Zhu Sun; Ying-Jie Xue; Dong-Sheng Wei; Xiang Li; Ya-Mei Zhang; Jian-Chun Qin (Natural Product Research, 2015)

The complete nucleotide sequence and genomic organization of a novel victorivirus with two non-overlapping ORFs, identified in the plant-pathogenic fungus Phomopsis vexans - Ru Jia Zhang; Jie Zhong; Hong Hong Shang; Xian Ting Pan; Hong Jian Zhu; Bi Da Gao (Archives of Virology, 2015)

Valproic Acid Alleviates Memory Deficits and Attenuates Amyloid-β Deposition in Transgenic Mouse Model of Alzheimer’s Disease - Ai-Guo Xuan; Xue-Bing Pan; Peng Wei; Wei-Dong Ji; Wen-Juan Zhang; Ji-Hong Liu; Le-Peng Hong; Wen-Liang Chen; Da-Hong Long (Molecular Neurobiology, 2015)

Positional variation in grain mineral nutrients within a rice panicle and its relation to phytic acid concentration - Da Su; Faisal Sultan; Ning-chun Zhao; Bing-ting Lei; Fu-biao Wang; Gang Pan; Fang-min Cheng (Journal of Zhejiang University-SCIENCE B, 2014)

Comparative genomic analysis provides insights into the evolution and niche adaptation of marine M agnetospira sp. QH ‐2 strain - Boyang Ji; Sheng‐Da Zhang; Pascal Arnoux; Zoe Rouy; François Alberto; Nadège Philippe; Dorothée Murat; Wei‐Jia Zhang; Jean‐Baptiste Rioux; Nicolas Ginet; Monique Sabaty; Sophie Mangenot; et al. (Environmental Microbiology, 2014)
Summary Magnetotactic bacteria ( MTB ) are capable of synthesizing intracellular organelles, the magnetosomes, that are membrane‐bounded magnetite or greigite crystals arranged in chains. Although MTB are widely spread in various ecosystems, few axenic cultures are available, and only freshwater M agnetospirillum spp. have been genetically analysed. Here, we present the complete genome sequence of a marine magnetotactic spirillum, M agnetospira sp. QH ‐2. The high number of repeats and transposable elements account for the differences in QH ‐2 genome structure compared with other relatives. Gene cluster synteny and gene correlation analyses indicate that the insertion of the magnetosome island in the QH ‐2 genome occurred after divergence between freshwater and marine magnetospirilla. The presence of a sodium‐quinone reductase, sodium transporters and other functional genes are evidence of the adaptive evolution of M agnetospira sp. QH ‐2 to the marine ecosystem. Genes well conserved among freshwater magnetospirilla for nitrogen fixation and assimilatory nitrate respiration are absent from the QH ‐2 genome. Unlike freshwater M agnetospirillum spp., marine M agnetospira sp. QH ‐2 neither has TonB and TonB ‐dependent receptors nor does it grow on trace amounts of iron. Taken together, our results show a distinct, adaptive evolution of M agnetospira sp. QH ‐2 to marine sediments in comparison with its closely related freshwater counterparts.

Glycosylation analysis of recombinant neutral protease I from Aspergillus oryzae expressed in Pichia pastoris - Da Lei; Yang Xu; Qinghua He; Yifeng Pan; Bo Chen; Liang Xiong; Yanping Li (Biotechnology Letters, 2013)

Immunomodulatory effects of dietary Bacillus coagulans in grouper (Epinephelus coioides) and zebrafish (Danio rerio) infected with Vibrio vulnificus - Chieh-Yu Pan; Yi-Da Wang; Jyh-Yih Chen (Aquaculture International, 2013)

Oxidative decarboxylation of mandelic acid derivative by recombinant Escherichia coli: a novel method of ethyl vanillin synthesis - Xiao-xia Pan; Jing-jing Li; Mei-gui Wang; Wen-sen He; Cheng-sheng Jia; Xiao-ming Zhang; Biao Feng; Da-li Li; Zeng Zeng (Biotechnology Letters, 2013)

Wnt/β-catenin signaling induces the aging of mesenchymal stem cells through promoting the ROS production - Da-yong Zhang; Yu Pan; Chong Zhang; Bing-xi Yan; Shan-shan Yu; Dong-ling Wu; Meng-meng Shi; Kai Shi; Xin-xiao Cai; Shuang-shuang Zhou; Jun-bo Wang; Jian-ping Pan; et al. (Molecular and Cellular Biochemistry, 2013)

Damage and management of cyclone Sidr-affected homestead tree plantations: a case study from Patuakhali, Bangladesh - Md. Zamiul Haq; Mahbub Robbani; Mohammad Ali; Md. Mainul Hasan; Md. Mahmudul Hasan; Md. Jashim Uddin; Monjila Begum; Jaime A. Teixeira da Silva; Xiao-Ying Pan; Md. Rezaul Karim (Natural Hazards, 2012)

Multi-environment mapping and meta-analysis of 100-seed weight in soybean - Ya-nan Sun; Jun-bo Pan; Xiang-lin Shi; Xiang-yu Du; Qiong Wu; Zhao-ming Qi; Hong-wei Jiang; Da-wei Xin; Chun-yan Liu; Guo-hua Hu; Qing-shan Chen (Molecular Biology Reports, 2012)

XPA A23G polymorphism and susceptibility to cancer: a meta-analysis - Jun Liu; Zhen Zhang; Xiao-Lin Cao; Da-Peng Lei; Zhong-Qiu Wang; Tong Jin; Xin-Liang Pan (Molecular Biology Reports, 2012)

Identification of potential serum biomarkers for Wilms tumor after excluding confounding effects of common systemic inflammatory factors - Jiaxiang Wang; Lei Wang; Da Zhang; Yuxia Fan; Zhankui Jia; Pan Qin; Jiekai Yu; Shu Zheng; Fuquan Yang (Molecular Biology Reports, 2012)

A novel genus of multicellular magnetotactic prokaryotes from the Yellow Sea - Ke Zhou; Wen‐Yan Zhang; Kui Yu‐Zhang; Hong‐Miao Pan; Sheng‐Da Zhang; Wei‐Jia Zhang; Hai‐Dong Yue; Ying Li; Tian Xiao; Long‐Fei Wu (Environmental Microbiology, 2012)
Summary Multicellular magnetotactic prokaryotes (MMPs) are a group of magnetotactic microorganisms composed of 10–40 Gram‐negative cells. Currently, all the identified MMPs show a spherical morphology and synthesize mainly iron sulfide magnetosomes. In this study, we report a novel genus of MMPs with peculiar ellipsoidal morphology and iron oxide magnetosomes, which were discovered in intertidal sediment of the Yellow Sea in China. Optical and fluorescence microscopy revealed that this organism was ∼10 × 8 µm in size and composed of ∼40 cells enveloped by an outer layer. Scanning electron microscopy showed that the cells were arranged in 4–6 interlaced circles. Bullet‐shaped magnetite magnetosomes were organized in chains roughly parallel to the long axis of the ellipsoidal MMPs when analysed by transmission electron microscopy. These MMPs displayed special escape motility, i.e. swimming rapidly from the edge to the centre of the droplet and then slowly back to the edge. In addition, they exhibited negative phototaxis. Light microscopy observations showed that the ellipsoidal MMPs reproduced by division along the body long axis. Both analysis of 16S rRNA gene sequence and fluorescence in situ hybridization revealed the ellipsoidal MMPs as a new genus of the Deltaproteobacteria . In summary, this novel genus of MMPs exhibit unique morphology, peculiar division process and distinct phylogenetic affiliation compared with the other MMPs.

Expression and identification of a thermostable malate dehydrogenase from multicellular prokaryote Streptomyces avermitilis MA-4680 - Zong-Da Wang; Bao-Juan Wang; Ya-Dong Ge; Wei Pan; Jie Wang; Lei Xu; Ai-Min Liu; Guo-Ping Zhu (Molecular Biology Reports, 2011)

Overexpression of CyclinD1 and underexpression of p16 correlate with lymph node metastases in laryngeal squamous cell carcinoma in Chinese patients - Zhi-jie Fu; Zhi-yong Ma; Qi-rong Wang; Da-peng Lei; Rong Wang; Chun-xi Liu; Xin-liang Pan (Clinical & Experimental Metastasis, 2008)

Hyper-spectral remote sensing to monitor vegetation stress - Hong-Yan Ren; Da-Fang Zhuang; Jian-Jun Pan; Xue-Zheng Shi; Hong-Jie Wang (Journal of Soils and Sediments, 2008)

Enhanced production of human Cytochrome P450 2C9 by Escherichia coli BL21(DE3)pLysS through the novel use of grey relational analysis and Plackett–Burman design - Da C. Hao; Pan H. Zhu; Sheng L. Yang; Ling Yang (World Journal of Microbiology and Biotechnology, 2007)

Genetic diversity within Oryza rufipogon germplasms preserved in Chinese field gene banks of wild rice as revealed by microsatellite markers - Li-Zhi Gao; Chi-Hong Zhang; Dao-Yuan Li; Da-Jian Pan; Ji-Zeng Jia; Yu-Shen Dong (Biodiversity and Conservation, 2006)

Optimization of Recombinant Cytochrome P450 2C9 Protein Production in Escherichia coli DH5α by Statistically-Based Experimental Design - Da C. Hao; Pan H. Zhu; Sheng L. Yang; Ling Yang (World Journal of Microbiology and Biotechnology, 2006)

Up-regulation interleukin-6 and interleukin-8 by activated protein C in lipopolysaccharide-treated human umbilical vein endothelial cells - Yi Li; Bin Du; Jia-qi Pan; De-chang Chen; Da-wei Liu (Journal of Zhejiang University-SCIENCE B, 2006)

Contributory presentations/posters - N. Manoj; V. R. Srinivas; A. Surolia; M. Vijayan; K. Suguna; R. Ravishankar; K. Suguna; A. Surolia; M. Vijayan; R. Schwarzenbacher; K. Zeth; Diederichs; et al. (Journal of Biosciences, 1999)